Transpedicular free-hand fixation in the subaxial cervical spine - Shamil Sh. Magomedov; Mikhail Yu. Dokish; Aleksandr P. Tatarintsev (Хирургия позвоночника, 2018)
Objective. To analyze the results of surgical treatment of patients with injuries and diseases of the cervical spine operated on using trans- pedicular fixation with free-hand technique. Matherial and Methods. A total of 97 patients with unstable injuries, congenital and acquired deformities, as well as with tumorous lesions of the cervical spine were examined. All patients were evaluated for the stability and reliability of transpedicular fixation in the long-term period, with the analysis of mistakes and complications that arose during treatment. Results. Positive results were obtained in 94.8 % of cases, and signs of fixation instability were absent in all patients. Despite 125 cases of pedicle wall perforation, only four patients required revision surgeries. A low rate of complications was noted, including no damage to the vertebral artery. The pain syndrome in patients decreased. Conclusion. The obtained results prove high efficiency and sufficient safety of the free-hand technique for the cervical spine fixation. At the same time, the technique requires careful preoperative preparation and examination of patients, thorough knowledge of anatomy of the operated area, and experience and qualification of the surgeon.